1998
DOI: 10.1016/s0002-9270(98)00408-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cholecystokininA receptors in transient lower esophageal sphincter relaxations triggered by gastric distension

Abstract: Loxiglumide significantly reduces the number of TLESRs triggered by gastric distension without interfering with swallow-related relaxation of the lower esophageal sphincter, suggesting the involvement of CCKA receptors in the reflex pathway mediating TLESRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…However, the currently available therapeutic modalities are not fast or effective enough to provide good control of postprandial heartburn. [26][27][28][29][30] In patients who consume antireflux medications only in response to acute heartburn, PPIs appear to have no value due to the time required to reach maximum efficacy. Consequently, PPIs are not considered a good therapeutic option for postprandial heartburn, leaving patients to utilize compounds such as antacids, Gaviscon, sucralfate, or H2RAs.…”
Section: Postprandial Heartburnmentioning
confidence: 99%
“…However, the currently available therapeutic modalities are not fast or effective enough to provide good control of postprandial heartburn. [26][27][28][29][30] In patients who consume antireflux medications only in response to acute heartburn, PPIs appear to have no value due to the time required to reach maximum efficacy. Consequently, PPIs are not considered a good therapeutic option for postprandial heartburn, leaving patients to utilize compounds such as antacids, Gaviscon, sucralfate, or H2RAs.…”
Section: Postprandial Heartburnmentioning
confidence: 99%
“…At present, there are only a few pharmacological agents (morphine, cholecystokinin, atropine, baclofen) available for the treatment of acid reflux (Boulant et al, 1997;Mittal et al, 1997;Penagini et al, 1997;Boeckxstaens et al, 1998;Clavé et al, 1998,), however it is very difficult to use most of these drugs because they need to be injected and /or they have side-effects. It is possible for only baclofen to be effective in the treatment of acid reflux and it has been reported that baclofen, a gamma-aminobutyric acid B agonist, has been successful in decreasing the rate of TLESRs, as well as decreasing the number of acid reflux episodes in healthy subjects and patients with GERD (Lidums et al, 2000;Zhang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…CCK-1(A) CCK-8 π (Boulant et al 1994;Clave et al 1998) Devazepide ª (Boulant et al 1994) Loxiglumide ª (Boeckxstaens et al 1998;Boulant et al 1997;Zerbib et al 1998) GABA B Baclofen ª (Blackshaw et al 1999;Lehmann et al 1999;Lidums et al 2000;Zhang et al 2002) Muscarinic Atropine ª (Mittal et al 1997;Lidums et al 1998) Methylscopolamine 0 (Fang et al 1999) Hyocine butylbromide 0 (Lidums et al 1997)…”
Section: Receptorsmentioning
confidence: 99%